ІДЕНТИФІКАЦІЯ ПОТУЖНОСТІ НЕБАЛАНСУ ТРИФАЗНОЇ ЧОТИРИПРОВІДНОЇ СИСТЕМИ ЖИВЛЕННЯ ДЛЯ ПОТРЕБ ЇЇ РОЗПОДІЛЕНОЇ КОМПЕНСАЦІЇ - Артеменко, М.Ю.; Чопик, В.В.; Михальський, В.М.; Шаповал, І.А.; Поліщук, С.Й. (Інститут електродинаміки НАН України, Київ, 2022)
The idea of distributed active filtration is to compensate for the currents of higher harmonics and undesirable components of the power of the main network with inverters of renewable energy converters of the connected microgrid, which have reserves of apparent power. For the convenience of distributed compensation, it is proposed to identify the sinusoidal mode of the three-phase four-wire power system, provided that the symmetric source is six mutually orthogonal components of the three-coordinate vector of line currents. The power of imbalance is shown to be due to four mutually orthogonal components of the three-coordinate vector of line currents with defined reference voltage vectors, each of which is proportional to a separate orthogonal component of the power of imbalance. Integral formulas for determining the scalar values of the four specified orthogonal components of imbalance powers have been obtained, which open the possibility of accounting for their contribution to the deterioration of the quality of electrical energy and the synthesis of control signals for active distributed filtration. The connection between the four specified orthogonal components of the power of imbalance and the parameters of the linear unbalanced load was established, which made it possible to verify these integral formulas using a computer experiment. It is analytically established and experimentally confirmed that the squares of the two orthogonal components of the imbalance powers associated with the current of the neutral wire are included in the decomposition of the square of apparent power and power losses with the multiplier, depending on the ratio of the resistances of the transmission line of the three-phase four-wire power system. References 17, figures 3.